Ethical requirement and financial interest: A literature review on socially responsible investing - Miriam von Wallis; Christian Klein (Business Research, 2015)
This paper provides an overview of the status quo in socially responsible investing (SRI) literature. We outline motives, history, and current best practice of SRI. We also provide a thorough analysis of a wide set of studies that cover two key topics in this field: the first research objective is to determine the relative performance of SRI vehicles in comparison to their conventional benchmarks. Our metaanalysis shows that most research studies find that socially responsible (SR) investments perform equal to conventional investments, but these findings are challenged by contradictory results from other studies. The second objective is to analyze SR behavior's effects on a company's financial results. We cover the period between 1986 and 2012. This paper provides future researchers with a well-documented and structured overview of the existing literature on SRI, thereby identifying gaps that might be closed by future research.
Keywords: M14; G11; 650; Socially responsible investing; SRI; Socially responsible investment; Ethical investment; Corporate social responsibility; Investment screens; Sustainable investments; Financial performance; Business ethics; Socially responsible rating approach